Similarity Search and Applications : 8th International Conference, SISAP 2015, Glasgow, UK, October 12-14, 2015, Proceedings - Amato, Giuseppe; Connor, Richard; Falchi, Fabrizio; Gennaro, Claudio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 8th International Conference on Similarity Search and Applications, SISAP 2015, held in Glasgow, UK, in October 2015. The 19 full papers, 12 short and 9 demo and poster papers presented in this volume were carefully reviewed and selected from 68 submissions. They are organized in topical sections named: improving similarity search methods and techniques; metrics and evaluation; applications and specific domains; implementation and engineering solutions; posters; demo papers. .
Keywords: Information storage and retrieva; Optical pattern recognition; Data structures (Computer scienc; Database management; Computer software; Electronic data processing; Information Storage and Retrieval; Pattern Recognition; Data Structures; Database Management; Algorithm Analysis and Problem Complexity; Numeric Computing